Ultrafast Pulsed Laser Induced Nanocrystal Transformation in Colloidal Plasmonic Vesicles. Issue 21 (2nd September 2018) - Karim, Mohammad Rezaul; Li, Xiuying; Kang, Peiyuan; Randrianalisoa, Jaona; Ranathunga, Dineli; Nielsen, Steven; Qin, Zhenpeng; Qian, Dong
Abstract: Plasmonic vesicle consists of multiple gold nanocrystals within a polymer coating or around a phospholipid core. As a multifunctional nanostructure, it has unique advantages of assembling small nanoparticles (<5 nm) for rapid renal clearance, strong plasmonic coupling for ultrasensitive biosensing and imaging, and near‐infrared light absorption for drug release. Thus, understanding the interaction of plasmonic vesicles with light is critically important for a wide range of applications. In this paper, a combined experimental and computational study is presented on the nanocrystal transformation in colloidal plasmonic vesicles induced by the ultrafast picosecond pulsed laser. Experimentally observed merging and transformation of small nanocrystals into larger nanoparticles when treated by laser pulses is first reported. The underlying mechanisms responsible for the experimental observations are investigated with a multiphysics computational approach featuring coupled electromagnetic/molecular dynamics simulation. This study reveals for the first time that combined nanoparticle heating and laser‐enhanced Brownian motion is responsible for the observed nanocrystal merging. Correspondingly, laser fluence, interparticle distance, and presence of water are identified as the most important factors governing the nanocrystal transformation. The guidelines established from this study can be employed to design a host of biomedical and nanomanufacturing applications involving laser interaction with plasmonic nanoparticles. Abstract : Understanding nanocrystal transformation during laser–material interaction has broad implications from laser nanomanufacturing of nanomaterials to retaining renal clearance capability of assembled nanostructures. This paper elucidates key contributing factors on nanocrystal transformation during interaction between plasmonic vesicles and ultrafast pulsed laser. With experimental observation and coupled electromagnetic field/atomistic simulation, this work establishes the conditions that nanocrystal transformation and merging occur.